PENGARUH PROFITABILITAS, LIKUIDITAS, STRUKTUR AKTIVA DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL (Studi Pada Perusahaan Transportasi di Bursa Efek Indonesia Tahun 2013-2018) - Dwi Nur Condro Prakoso; Rita Kusumawati (Proceedings University of Muhammadiyah Yogyakarta Undergraduate Conference, 2022)
This study aims to analyze the Effect of Profitability, Liquidity, Assets Structure and Company Size on Capital Structure. The object of this research is transportation companies listed on the Indonesian Stock Exchange in 2013 – 2018. In this study, the sample used amounted to 166 samples in a period of 6 years using purposive sampling method. The type of data used is secondary data obtained from the company's financial statements downloaded through the official website of the Indonesia Stock Exchange. Based on the results of this study shows that variable profitability and company size have no effect on capital structure while variable liquidity and asset structure negatively effect and significant on capital structure.